Foreign direct investment in cross-border infrastructure projects - Kwok-Chiu Fung; Alicia Garcia-Herrero; Francis Ng (Asian Development Bank Institute (ADBI), 2011)
In this paper we critically review the relevant information and literature that can enhance the feasibility and the successful implementation of cross-border infrastructure projects. We provide detailed information concerning foreign direct investment in the major emerging regions: East Asia and the Pacific, Latin America, and Eastern Europe. We also discuss the theoretical and empirical literature which sheds light on the characteristics of transnational infrastructure projects, who should conduct them, and what determines their existence. The literature points to the importance of government involvement in transnational infrastructure projects as there are clear external benefits which will otherwise not be reaped. It also points to the importance of coordination for the success of the project. The Asian Development Bank is well placed to perform that role. Lastly, we provide six cases of cross-border infrastructure projects, two each from East Asia, Latin America, and Eastern Europe. These cases illustrate the critical need for smooth coordination of the diverse groups of team players, top-level backing of the projects, as well as a thorough understanding of all the political and financial factors involved that can influence the success of these projects.
Keywords: O19; F15; F36; R58; 330; Infrastrukturinvestition; Grenzüberschreitender Verkehr; Internationale Zusammenarbeit; Schwellenländer; Welt